Local Elections, Local Actors And Political Patronage Networks (Understanding Involvement Of Coal Mining Bosses In The Local Elections In South Kalimantan Province - Murdiansyah Herman; Muhammad Uhaib As’ad (Indonesian Association for Public Administration (IAPA), 2018)
This article analyses the political drama of the fall Soeharto's government in May 1998, after 32 years in power, has made a new era of this country democratic life. The fall of the Soeharto’s government which gave to a new era of democratization has changed of political landscape from the authoritarian system to the transition of democracy. The democratic transition has had an impact on the almost uncontrollable political dynamics. It also provides an opportunity for central and local political actors to consolidate power and reposition themselves to capture of power institutions and democratic institutions through contestation of local elections. In the capitalization democracy, political pragmatism structured in democratic behavior has spawned the costly cost of democracy. Therefore, it has become a fact in the current reality of democracy that political actors who occupy the stage of democracy are people who have capital (money) or background as entrepreneurs. The involvement of mine bosses in the local elections in South Kalimantan as sponsors of political fund or as candidats local rulers has spawned a black market of democracy characterized by political concessions and transactions through a network of political patronage. South Kalimantan is known as a coal mining product, mining issues in the local election became political marketing to build political patronage networks among local actors. In the context of open competition in local elections, the issue of political funding becomes the most crucial in the democratic transition. The political brokers will position themselves as shadow government after local election in government and become as a controler in policy government, especially mining policy. The mine bosses have of bergaining position in the political landscape and political patronage network to place the people who occupy the position of the local head by power money and oligarchy of political party. The heads of political parties or political elites in South Kalimantan are majority as mine bosses. Thus, the existence of political parties has been taken drive by capitalist . The cartelization politiacal parties became clearer in the lead up to the elections in which party institutions had become the arena of conspiracy between party regimes and local ruling candidates or local power.